2022
DOI: 10.3390/tomography8060223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Benignity and Malignancy of BI-RADS 4 Breast Lesions Based on a Combined Quantitative Model of Dynamic Contrast-Enhanced MRI and Intravoxel Incoherent Motion

Abstract: The aim of this study was to explore whether intravoxel incoherent motion (IVIM) combined with a dynamic contrast–enhanced magnetic resonance imaging (DCE–MRI) quantitative model can improve the ability to distinguish between benign and malignant BI-RADS 4 breast lesions. We enrolled 100 patients who underwent breast MRI at our institution and extracted the quantitative parameters of lesions with a post-processing workstation. Statistical differences in these parameters between benign and malignant BI-RADS 4 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This may be related to the abundant capillaries in the stroma of malignant diseases. However, a study conducted by Xu et al reached the opposite conclusion [ 33 ]. In addition, the AUC of Dp value in our study surpassed the results reported by He et al, which may be attributed to differences in the selection of the b-values used for data calculation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the abundant capillaries in the stroma of malignant diseases. However, a study conducted by Xu et al reached the opposite conclusion [ 33 ]. In addition, the AUC of Dp value in our study surpassed the results reported by He et al, which may be attributed to differences in the selection of the b-values used for data calculation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%